Engaging English language learners in digital multimodal composing: Pre-service teachers' perspectives and experiences. (1st June 2022) - Tour, Ekaterina; Barnes, Melissa
Abstract: Language learners often require appropriate scaffolding to engage in digital multimodal composing to maximise its potential for learning. This illuminates the need for pre-service teachers to be ready for these experiences both on teaching placements and at the beginning of their careers. However, little is known about their readiness for digital multimodal composing in linguistically and culturally diverse classrooms. Drawing on a case study of an after-school program for primary school English as an Additional Language (EAL) students, facilitated by four pre-service teachers, this article explores their perspectives on engaging EAL students in digital multimodal composing. The study found that pre-service teachers recognised that digital multimodal composing is valuable for language learners; however, they struggled to name more specific literacy benefits afforded by digital multimodal composing. For all participants in this study, students' engagement with digital interfaces stood out as the main challenge but they had limited concerns about other aspects of digital multimodal composing. While they effectively scaffolded students' learning in relation to the challenges that they recognised using more general pedagogical approaches, other dimensions of digital multimodal composing were often left unattended. The article concludes with a number of implications for preparation of teachers working with language learners.